2019
DOI: 10.3390/agriculture9030067
|View full text |Cite
|
Sign up to set email alerts
|

Sowing Date Affects Maize Development and Yield in Irrigated Mediterranean Environments

Abstract: Timely sowing is critical for maximizing yield for both grain and biomass in maize. The effects of early (mid-March), normal (mid-April), and late (mid-May) sowing date (SD) were studied over a three-year period in irrigated maize under Mediterranean conditions. Early SD increased the number of days from sowing to plant emergence. Late SD reduced the number of days to plant maturity, and had higher forage yields, higher grain humidity, and taller plants. The average grain and forage yields achieved were 13.2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
(56 reference statements)
1
19
1
Order By: Relevance
“…(Table 5). However, contrary to our observation, Shrestha et al (2016) and Maresma et al (2019) reported shorter days to silking, for late than for early planting.…”
Section: Interaction Effects Of Temperaure Variety and Planting Datecontrasting
confidence: 99%
“…(Table 5). However, contrary to our observation, Shrestha et al (2016) and Maresma et al (2019) reported shorter days to silking, for late than for early planting.…”
Section: Interaction Effects Of Temperaure Variety and Planting Datecontrasting
confidence: 99%
“…The effect of the temperatures in April (mnt4) on the final yield was not surprising; growers tend to sow as early as they can, and the years with favorable conditions in the first decade of April provide them with a head-start that can affect their yields at the time of harvest by providing the crop with the more time to photosynthesize and avoiding the drought in the critical period of flowering (MARESMA et al, 2019). Precipitation in May and July are crucial in alleviating the harsh temperature conditions and providing the better conditions in the most critical moment in the vegetative cycle -flowering, therefore affecting the pollination, kernel number and seed set as the components of the yield.…”
Section: Resultsmentioning
confidence: 99%
“…Two maize varieties of different FAO cycles were sown: Cecilia (600 FAO) and Eleonora (700 FAO). These cultivars are representative of FAO cycles 600 to 700, which are commonly grown in the area and often used as controls for varietal studies (Maresma, Ballesta, et al, 2019; Serra, Voltas, López, Capellades, & Salvia, 2007; Sisquella, Lloveras, Álvaro, Santiveri, & Cantero, 2004). Conventional tillage was carried out before sowing as for the winter crops.…”
Section: Methodsmentioning
confidence: 99%
“…Normally, a summer crop (maize or sorghum) is grown from June to October, and thereafter, a winter cereal is sown in November (Maresma, Martinez‐Casanovas, et al, 2019). In mild areas, maize is widely used, and its sowing date is important to maximize yield potential and forage quality (Maresma, Ballesta, Santiveri, & Lloveras, & Lloveras, J., 2019). Also, winter cereals or Italian ryegrass are the most common winter crops in the double‐annual cropping systems destined to forage production (Grignani et al., 2007; Moule, 1980).…”
Section: Introductionmentioning
confidence: 99%